Vibrational assignments of two polymorphic forms of metaxolone by using DFT calculations and the SQM methodology - Iramain, Maximiliano Alberto (2018)
A theoretical study has been performed on the musclerelaxant 5-[(3, 5-dimethylphenoxy)methyl]-1,3-oxazolidin-2-one, of generic name metaxolone (MTX), by using the hybridB3LYP/6-31G calculations in the gas phase and theexperimental available infrared and Raman spectra in thesolid phase. Three C1, C2 and C3 isomers were found in thepotential energy surface (PES) but only two of them, C1 andC2 correspond to those experimentally reported polymorphicforms A and B, respectively. The absence of C3 isomer couldbe easily explained by the quite high values in the dihedralC5-C7-O2-C9 and O1-C5-C7-O2 angles different from thoseexperimental structures reported for the two polymorphicforms A and B of MTX. On the other hand, the higher bondorders values together with the high topological propertiesobserved for the oxazolidinone ring of C1 could possiblysupport their existence despite this isomer has highest energythan C2 and C3. The natural bond orbital (NBO) analysesreveal the high stabilities of C1 and C2 while the atoms inmolecules(AIM) study suggests that the ringdimethylphenoxy-methyl practically do not have influence onthe properties of MTX. The frontier orbitals show that theisomers of MTX have reactivities and electrophilicity indexessimilar to antiviral thymidine while their nucleophilicityindexes present values closer to antimicrobial thione. Inaddition, the complete vibrational assignments of those twostable isomers were performed by using the experimentalavailable FT-IR and FT-Raman spectra, their normal internalcoordinates,the scaled quantum mechanical force field(SQMFF) methodology and the Molvib program.Theharmonic force fields for the two isomers and theircorresponding force constants were also reported. The forceconstants values are in agreement with values reported in theliterature for species with similar groups.